A PATHWAY TO HOMEOWNERSHIP? EVIDENCE FROM THE IMMIGRATION REFORM AND CONTROL ACT OF 1986. (4th December 2019) - Sharpe, Jamie
Abstract : The impact of legal status on economic outcomes has been well documented in the literature with most research focused on labor market outcomes such as wages and occupational mobility. In this paper, I utilize the exogenous variation created the Immigration Reform and Control Act (IRCA) of 1986 to estimate the effect of amnesty polices on homeownership among undocumented immigrants. Using a regression discontinuity framework, the results suggest that the IRCA increased homeownership rates of eligible immigrants by around 4 percentage points relative to ineligible immigrants. Moreover, an extension to the main analysis suggests that immigrants ineligible for the IRCA adjusted their household formation by increasing the rates of coresidency. ( JEL J61, R23, R31)